Robust adaptive vibration control for a string with time‐varying output constraint. (12th October 2018) - He, Wei; Jing, Zhe; He, Xiuyu; Liu, Jin‐Kun; Sun, Changyin
Summary: In this paper, we present the vibration control design for a string with the boundary time‐varying output constraint. The dynamics of the string is a distributed parameter system described by a partial differential equation and two ordinary differential equations. A barrier Lyapunov function with a logarithmic function is adopted to prevent the time‐varying constraint violations. Adaptive control is designed to handle the system parametric uncertainties. Stability analysis and the solvability of the inequality equations are provided. Numerical simulations are provided to illustrate the effectiveness of the proposed control design.